Report on the Observance of Standards and Codes on Accounting and Auditing Update : Georgia - World Bank Group (World Bank, Vienna, 2015)
Reports on the Observance of Standards and Codes (ROSC) Accounting and Auditing (AA) assess accounting and auditing practices in participating countries. They form part of a World Bank and International Monetary Fund joint initiative to review the quality of implementation of twelve internationally recognized core standards relevant to economic stability and private and financial sector development (the ROSC Program). Since its inception in 2000, the ROSC AA program has concluded evaluations of the AA environment in more than one hundred countries around the world. ROSC AA reports have been produced for all countries of the Europe and Central Asia Region, except Russia. This report covers the accounting, audit, and financial reporting frameworks as a whole, paying particular attention to the financial sector, state owned enterprises, SMEs and audit regulation - key areas that are important in the current economic context of Georgia. With respect to SOEs, the report focuses on the existing requirements, standards enforcement, and use of financial reports and statutory audit findings by the Government in its decision making and monitoring of SOEs. This report also discusses SMEs existing financial reporting requirements, and the need to simplify the requirements for the small and micro businesses. Finally, the report reviews the audit oversight function and a quality assurance system soon to be employed by Georgia, and provides recommendations to raise the quality of audit services through the strengthening of audit oversight.